THE EFFECT OF DER, SALES GROWTH ON ROA IN RETAIL COMPANIES LISTED ON THE IDX IN 2021-2025 - Restu Permatasari; Didin Rasyidin Wahyu; Ombi Romli (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
ROA is used to measure efficiency, indicating how well a company utilizes its assets to generate net profit. This study aims to determine the effect of Debt-to-Equity Ratio (DER) and Sales Growth on Return on Assets (ROA) in retail companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2025 period. This study employs a quantitative research method. Quantitative research can be defined as a method grounded in the philosophy of positivism, used to study specific populations or samples; it involves data collection via research instruments and quantitative or statistical data analysis to describe phenomena and test established hypotheses. Purposive sampling was used as the sampling technique. Based on the established criteria, a sample of 9 companies was obtained. Secondary data were used, collected via the documentation method by accessing data from www.idx.co.id and www.idn.financial.com. The data analysis technique employed was quantitative research with a descriptive approach. The research results indicate that (H1) significant value = 0.000 < 0.05 then H1 was accepted and H0 rejected (H2) significant value = 0.012 < 0.05 then H2 was accepted and H0 rejected (H3) significant value = 0.000 < 0.05 or significant <0.05 andFcount > Ftable or Fcount = 24,660 and Ftable 0.000 then H3 is accepted and H0 is rejected. The study concludes that DER has a significant partial effect on ROA, and Sales Growth also has a partial effect on ROA. Furthermore, DER and Sales Growth collectively (simultaneously) have a significant effect on ROA.